Pengembangan Ekonomi Masyarakat Berbasis Teknologi - Heny Handayani (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
The purpose of this community service is to see firsthand the potential possessed by Bandung Regency, we will be shown with very good potential, especially in the field of the creative economy which may be able to develop the lives of the people of the Mekarmanik village better. There is one thing that is in the spotlight, namely the limited knowledge of existing technologies such as cellphones, how to access E-commerce, etc. The method of stages carried out in this community service such as analyzing the economic sector, counseling on increasing production, and health counseling followed by control. Furthermore, training on improving potential sectors and providing knowledge about changing business trends electronically in the industrial era 4.0. Based on the stage of community service activities that the target community has received the material presented in general, it can be said that this activity program is successful. The community has received counseling and training regarding technology-based economic development, including by providing knowledge and online business development, analyzing the growth of internet users and smartphone or gadget users so that participants are able to become technopreneur practitioners.